The mechanotransducer Piezo1 coordinates metabolism and inflammation to promote skin growth - Yingchao Xue; Elizabeth Winnicki; Zhaoxu Zhang; Ines Lopez; Saifeng Wang; Charles Kirby; Sam S. Lee; Ang Li; Chaewon Lee; Hana Minsky; Kaitlin Williams; Kevin Yueh-Hsun Yang; et al. (Nature Communications)
Abstract The skin has a remarkable ability to grow under constant stretch. Using a controlled tissue expansion system in mice, we identified an enhanced inflammatory-metabolic network in stretched skin via single-cell RNA sequencing, flow cytometry and spatial transcriptomics. Stretched epidermal cells exhibit heightened cellular crosstalk of CXCL, CCL, TNF, and TGF-β signaling. Additionally, skin expansion increases macrophage and monocyte infiltration in the skin while altering systemic immune cell profiles. Glycolysis-related genes, including Glut1 and Aldoa were significantly elevated. We hypothesize that Piezo1, a non-selective calcium-permeable cation channel, senses tension in stretched skin, driving these responses. The epidermal-Piezo1 loss-of-function animals show reduced skin growth, tissue weight, tissue thickness, macrophage infiltration, and glycolysis activity. Conversely, animals with a pharmacological Piezo1 gain of function exhibit an increase in these factors. Our findings highlight the coordinating role of Piezo1 for metabolic changes and immune cell infiltration in tension-induced skin growth.